Framework for Assessing Effectiveness of Peak Hour Parking Restrictions: Case Study from Washington, D.C. Issue 1 (2016) - Elahi, Manzur; Steverson, Gregg; Dey, Soumya; Dock, Stephanie; Green, Larry
Roadways provide mobility for goods and services and accessibility to destinations. In urban settings such as the District of Columbia, an important element of accessibility is the ability to park on the street close to the destination. Agencies often use peak hour parking restrictions as a strategy to balance these two often-conflicting goals. The District Department of Transportation undertook a research project to develop a framework for assessing the effectiveness of existing peak hour parking restrictions and evaluating the effects of any modifications. The framework was developed, tested, and applied to two major corridors: Connecticut Avenue and Rhode Island Avenue. The corridors were modeled to simulate the existing restrictions and the alternatives. The corridor level of service was used to measure the mobility and determine the desired restriction periods. In addition, the study evaluated the effects of any restriction changes on relevant factors, such as land use, transit availability, neighborhood parking, and cut-through traffic. A policy framework and an implementation plan were developed as part of this study, and they can be applied to other corridors. These findings can be useful for jurisdictions considering the reevaluation of their peak hour parking restriction policies.